Analysis of Ordinary Least Square and Geographically Weighted Regression on the Human Development Index of North Sumatra 2021 - Nurhalizah; Pardomuan Sitompul (Formosa Journal of Applied Sciences, 2022)
The Human Development Index has a big contribution to human development in a region, the HDI value is useful for the government as development planning and allocating funds to improve welfare. This research will look for the HDI model in North Sumatra with OLS and GWR, as well as look at the factors that have the greatest influence on HDI in North Sumatra in 2021. Based on the analysis carried out using OLS, one model for the HDI for North Sumatra province with the largest parameter value is the average value. average length of school. Using the GWR, 33 HDI models were obtained for each district/city in North Sumatra. Furthermore, by using OLS and GWR on HDI in North Sumatra, it is obtained that the factor that has the greatest influence on HDI scores in North Sumatra by looking at the value of the largest parameter estimator is the average length of schooling.